2015
DOI: 10.1128/iai.00217-15
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD4+Foxp3+Regulatory T Cells in Protection Induced by a Live Attenuated, Replicating Type I Vaccine Strain of Toxoplasma gondii

Abstract: Toxoplasmosis is caused by a protozoan parasite that infects humans and other warm-blooded animals. Infections in humans are generally asymptomatic, although immunosuppressed patients may exhibit severe symptoms. Similarly, primary infection during pregnancy can lead to miscarriage and neonatal malformations. Toxoplasmosis can be transmitted to humans via ingestion of oocysts or via the consumption of meat products contaminated with tissue cysts (1). Effective vaccination of domestic livestock can therefore pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
3
4
0
Order By: Relevance
“…7 j) and T Reg numbers in MLN and lamina propria were not increased by IL2C injections (Fig. 7 k–m) suggesting a role for IL2C pre-treatment independent of the previously reported T Reg expansion with JES6-1A12-containing IL2C 40 , 41 . Collectively, these results demonstrate a protective role of IL2C pre-treatment in acute lethal murine toxoplasmosis that is dependent on IL-12, IL-18 and IFN-γ but is independent from effects on parasite burden.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…7 j) and T Reg numbers in MLN and lamina propria were not increased by IL2C injections (Fig. 7 k–m) suggesting a role for IL2C pre-treatment independent of the previously reported T Reg expansion with JES6-1A12-containing IL2C 40 , 41 . Collectively, these results demonstrate a protective role of IL2C pre-treatment in acute lethal murine toxoplasmosis that is dependent on IL-12, IL-18 and IFN-γ but is independent from effects on parasite burden.…”
Section: Resultssupporting
confidence: 57%
“…Using JES6-1A12-containing IL2C, Akbar et al 41 showed that selective expansion of T Reg cells in Type I T. gondii RH-infected animals improved control of the parasite. It was also demonstrated that T Reg expansion with JES6-1A12-containing IL2C can overcome the competition for bioavailable IL-2 by regulatory and effector T cells, leading to reduced immunopathology and morbidity during acute Type II T. gondii ME49 infection 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent report showed an increase in the Treg response after infection with the vaccine strain. This increase was temporary and was followed by increases in Treg effector cells, which were correlated with T. gondii control . Our data show that rMAG induced a significant increase in Treg in CIP, an interesting finding due to the relevance of this subpopulation in the control of T. gondii infection.…”
Section: Discussionsupporting
confidence: 60%
“…At 9 days after infection, IL2C pre-treated mice displayed significantly reduced gross pathology of gut and liver (Fig 7G, H) in the absence of any effect on parasite burden (Fig 7I). TReg numbers in MLN and lamina propria (LP) were not increased after IL2C injections (Fig 7J, K, L) suggesting a role for IL2C pre-treatment independent of the previously reported TReg expansion with JES6-1A12-containing IL2C [40,41]. Collectively, these results demonstrate a protective role of IL2C pre-treatment in acute lethal murine toxoplasmosis.…”
Section: Il2c Pre-treatment Protects Mice From Acute Lethal Toxoplasmsupporting
confidence: 58%
“…Using JES6-1A12-containing IL2C, Akbar et al [41] showed that selective expansion of TReg cells in Type I T. gondii RH-infected animals improved control of the parasite. It was also demonstrated that TReg expansion with JES6-1A12-containing IL2C can overcome the competition for bioavailable IL-2 by regulatory and effector T cells, leading to reduced immunopathology and morbidity during acute Type II T. gondii ME49 infection [40].…”
Section: Interventionsmentioning
confidence: 99%